Speed Control of quadcopter motors for a dynamic Stability - علي, حنكه; صفاء, بوذينة; نعيمة, حريشة (University of El-Oued, 2022)
"Recent years have witnessed a qualitative leap that affected all areas of life: political, social, and technological. Where are the manifestations of this development varied from one field to another, and the technology of drones obtained its significant share of this development to enter the civil field from its wide door, to have a major role in serving the humanitarian community and focusing on the vital areas that are related to the daily life of the human being for the purpose of sharing the effort with the human element and paying the risks that may be exposed to it while performing some tasks. This work aims to speed control of quadcopter BLDC motor for dynamic stability. For this purpose, the mathematical model of the BLDC motor associated with the inverter was implemented in Simulink Matlab software, as well as for the control of speed and angle in order to ensure stability when flying. After the modeling and simulation, we extract the data model based on experimentally testing for the mechanical and electrical data modeling in order to obtain a model closer to real machine and to obtain optimum regulator parameters more stable system in speed or angle control. Finally, we carried out the experimental work in real-time, where the results showed the effectiveness and efficacy of the proposed control for this study." "شهدت السنوات الأخيرة نقلة نوعية مست كل مجالات الحياة: السياسية، الاجتماعية والتكنولوجية. حيث اختلفت مظاهر هذا التطور من مجال إلى آخر، وقد نالت تكنولوجيا الطائرات بدون طيار نصيبها المعتبر من هذا التطور لتدخل إلى المجال المدني من بابه الواسع، ليكون لها دور كبير في خدمة المجتمع الإنساني والتركيز على المجالات الحيوية التي ترتبط بالحياة اليومية للإنسان بغرض تقاسم الجهد مع العنصر البشري ودفع المخاطر التي قد يتعرض لها أثناء أداء بعض المهام. يهدف هذا العمل إلى التحكم الديناميكي في محرك BLDC الخاص بالطائرة الرباعية ذاتية القيادة من أجل هذه الغاية قمنا بالنمذجة الرياضية للمحرك مع المحول العكوس وتم تنفيذ هذه النمذجة في برنامج Simulink Matlab"" ""، كذلك بالنسبة للتحكم في السرعة والزاوية من أجل ضمان الاستقرار عند الطيران. بعد النمذجة والمحاكاة قمنا بالكشف التجريبي لبيانات المحرك من أجل الحصول على نموذج أكثر قربا للحقيقة، والحصول على إعدادات تحكم أكثر استقرار سواءا من أجل التحكم في السرعة أو الزاوية. وفي الأخير قمنا بالعمل التجريبي في الوقت الحقيقي وأظهرت النتائج مدى فعالية ونجاعة التحكم المقترح من أجل هذه الدراسة. "
مذكرة ماسترتخصص تحكم كهربائي
Keywords: Keywords: Brushless Motor, Speed control Dynamic stabilization of Quad-copter, Experimental test, Data modeling.; محرك بدون مستشعرات موضع، مراقبة السرعة، الاستقرار الديناميكي للمروحية الرباعية، الاختبار التجريبي، نمذجة المعطيات.